The Physical and Functional Properties of Partially Defatted Coconut Testa Flour - Yalegama, Chandi; Marasinghe, S. S. K.; Pathirana, D. T. H.; Marikkar, J. M. N. (International Coconut Community, 2021)
Coconut testa is an important byproduct of the coconut industry. In this study, particle size distribution, physical and functional properties of flour produced from partially coconut testa of four local cultivars namely san raman, gon thembili, ran thembili, TallxTall were compared with those of commercial hybrid (COM) using relevant procedures. Results showed that particle size distribution, physical and functional properties of flours of different coconut cultivars were varied significantly (p<0.05). The highest bulk density value was observed for SR (0.67 g/ml) while the lowest for TxT (0.54 g/ml) (p<0.05). Maximum swelling capacity (35.00 ml) and oil absorption capacity (142.67%) were recorded for COM while the least swelling capacity (20.67 ml) and oil absorption capacity (85.67%) were recorded for RT (p<0.05). The highest emulsion activity was found for COM (50.00%) while the least value recorded for SR (42.95) (p<0.05). The maximum emulsion stability was displayed by COM (54.86%) while the least emulsion stability was recorded for GT (27.51%) (p<0.05). The observed physical properties suggested that coconut testa flour of COM variety has certain advantages over others. It could be used for partial replacement with wheat flour for value addition leading to non-cereal based products.